Analisis faktor-faktor yang mempengaruhi pertumbuhan kredit konsumsi serta pengaruhnya terhadap pertumbuhan ekonomi di Indonesia - Irfan, Muhammad Fadillah; ', Syapsan; ', Rosyetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Consumer credit growth at commersial bank in Indonesia has significantimprovement during the last few years. Market share of consumer credit iscontinues to grow and even since 2003 exactly, it’s portion within creditportofolio of commercial bank had exceeded the investment credit. With rapid growth, consumer credit become to concern of government nowadays. The government worried great quantity of consumer credit can has an impact that will not be good for the economy. However, some people opine that consumer credit also has a positive effect on the economy. This research have goal to know and analyze factors are influencing consumer credit and also to know how credit consumer is influencing the economic growth. The data used in this research is secondary data that contitute an annual time series data period 2000-2013. The data used include consumer credit amount, consumer credit interst rate, dependency ratio, income per capita, inflation and economic growth. For data analyze used OLS (Ordinary Least Square) method with SPSS 17.0 software help. The estimated result show that consumer credit interst rate, dependency ratio and income per capita have significant influence to consumer credit. While inflation does not significantly affect consumer credit. Calculation results R Square value is 0.994. Its mean 99,4 percent consumer credit growth can be explained by four independent variables. While the remaining 0,6 percent explained by other variables outside the model. The second model show that consumer credit has positive and significant influence to Indonesian economic growth. R2 value in the amount of 0.461 means alteration of economic growth value influenced by alteration of consumer credit value in commercial banks in Indonesia.Keywords : Consumer Credit, Interst Rate, Dependency Ratio, Income per capita, Inflation, Economic Growth